Fibula single-tunnel versus fibula double-tunnel for both anterior talofibular ligament and calcaneofibular ligament reconstruction: a biomechanical comparison - Gan, Jingyue; Liang, Haifeng; Li, Dongtai; Yan, Yiran; Liu, Zhongxun; Chen, Yan; Yu, Bo (BMC musculoskeletal disorders, 2025)
Background Anatomic ligament repair surgery, despite being a tremendous technical challenge in treating chronic lateral ankle instability patients, remains the gold standard for this condition. The fibula single-tunnel and double-tunnel techniques are effective for intraoperative reconstruction of the anterior talofibular ligament (ATFL) and calcaneofibular ligament (CFL). However, which approach is more appropriate is a subject of debate. Methods Twelve fresh frozen cadaveric ankles were randomly divided into 2 groups of 6 specimens: fibula single-tunnel reconstruction group and fibula double-tunnel reconstruction group. The specimens were tested for ankle joint laxity on the plane radiographs with 150 N anterior drawer force and 150 N varus stress force. The anterior talar displacement and talar tilt angle were measured at states of intact, cut and reconstruction of both ATFL and CFL. Then, the reconstructed specimens were loaded to ultimate failure to determine the strength and stiffness of each construct. Results There were no significant differences between the two groups in the anterior talar displacement and talar tilt angle at the states of intact, cut and reconstruction of both the ATFL and CFL. There were no significant differences between the two groups in the ultimate load failure and stiffness after reconstruction of both the ATFL and CFL. Conclusions In patients undergoing ligament reconstruction surgery for ankle instability, both single-tunnel reconstruction of the fibula and double-tunnel reconstruction of the fibula were able to achieve better results. There was no significant difference between these two surgical procedures in our study. The long-term survival of the ankle joint after both techniques remains to be studied.